Design of a large area digital SiPM with high fill factor and fully serial digital readout for single photon detection in liquid noble gas detectors - Fischer, Peter; Keller, Michael; Ritzert, Michael (Journal of Instrumentation, 2025)
We present a 'digital SiPM' photo-detection chip combining single photon sensitive avalanche photo diodes and CMOS readout electronics on a single die. The chip has a size of 8046× 9032 μm2 with 72.5% of photo sensitive area. It is subdivided into 32 × 30 pixels with an average size of 250×291 μm2. For each photon hit, the chip records the pixel coordinate and the arrival time with a granularity of ≈ 10 ns. Readout and chip control are purely digital, requiring only 4 CMOS signals. Several chips can be daisy chained and grouped on larger modules so that detector planes with ≈ 70% photo sensitive area can be build. Our chip may be used in experiments that need to detect rare scintillation events, for instance dark matter searches using liquid noble gases.